2010
DOI: 10.1128/jcm.01129-10
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Methicillin-Resistant Staphylococcus aureus Anovaginal Colonization in Pregnant Women in 2005 versus 2009

Abstract: In 2005, the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) anovaginal colonization in pregnant women at our center (Columbia University Medical Center) was 0.5%, and MRSA-colonized women were less likely to carry group B streptococcus (GBS). In this study, our objectives were to identify changing trends in the prevalence of MRSA and methicillin-susceptible S. aureus (MSSA) anovaginal colonization in pregnant women, to assess the association between MRSA and GBS colonization, and to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…5,[21][22][23] Maternal vaginal MRSA colonization rates of 0.4 to 0.6% support this hypothesis, but concurrent maternal MSSA vaginal colonization prevalence of nearly 20-fold that of MRSA is contradictory. 24,25 This issue is further compounded by contradictory data in different reports noting cesarean section or vaginal delivery as risk factors supporting CA-MRSA colonization. 26,27 In a report by Saiman et al describing hospital transmission of CA-MRSA in postpartum women, infections presented at a mean of 23 days (range 4 to 73), suggesting that the latent period between exposure and disease with MRSA may be longer than previously appreciated.…”
Section: Mssa Versus Mrsa Tracheal Colonization and Pneumoniamentioning
confidence: 87%
“…5,[21][22][23] Maternal vaginal MRSA colonization rates of 0.4 to 0.6% support this hypothesis, but concurrent maternal MSSA vaginal colonization prevalence of nearly 20-fold that of MRSA is contradictory. 24,25 This issue is further compounded by contradictory data in different reports noting cesarean section or vaginal delivery as risk factors supporting CA-MRSA colonization. 26,27 In a report by Saiman et al describing hospital transmission of CA-MRSA in postpartum women, infections presented at a mean of 23 days (range 4 to 73), suggesting that the latent period between exposure and disease with MRSA may be longer than previously appreciated.…”
Section: Mssa Versus Mrsa Tracheal Colonization and Pneumoniamentioning
confidence: 87%
“…In several recent reports, anovaginal S. aureus colonization was identified in 10 to 25% of pregnant women. [16][17][18][19][20] MRSA isolates were only identified in 0.5 to 10.4% of these women.…”
Section: Development Of Antibiotic Resistancementioning
confidence: 95%
“…[22] Similarly, Top et al reported MSSA and MRSA anovaginal colonization rates of 11.8% and 0.6%, respectively, in pre-partum women, although neonatal colonization was not assessed. [23] These findings suggest that vertical transmission of S. aureus occurs, but is more relevant for MSSA than MRSA, presumably because fewer women are colonized with MRSA.…”
Section: Discussionmentioning
confidence: 99%